(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the role and importance of trade unions as a specific part of a non-profit organization. Trade unions are one of the largest public associations. Trade unions express and protect the socio-economic rights and legitimate interests of workers working at individual enterprises, institutions, and organizations.